The effects of telerehabilitation on physiological function and disease symptom for patients with chronic respiratory disease: a systematic review and meta-analysis - Yue Dai; Hao Huang; Yuchen Zhang; Na He; Min Shen; Hong Li (BMC Pulmonary Medicine, 2024)
Abstract Objective To compare the impact of telerehabilitation versus conventional rehabilitation on the recovery outcomes of patients with chronic respiratory disease (CRD). Methods The Cochrane Library, MEDLINE, Web of Science and Embase were searched to collect randomized controlled trials (RCTs) on telerehabilitation for the rehabilitation of patients with chronic respiratory system diseases since the establishment of the database to November 14, 2023. Two researchers independently screened the literature and extracted valid data according to the inclusion criteria. The quality assessment of included studies was conducted individually by using the RoB 2(Risk of Bias 2) tool, followed by meta-analysis using RevMan5.3 software. Results Based on inclusion and exclusion criteria, 21 RCTs were included, comprising 3030 participants, with 1509 in the telerehabilitation group and 1521 in the conventional rehabilitation group. Meta-analysis results indicated that compared to conventional rehabilitation, video conference-based telerehabilitation demonstrated significant improvements in short-term (≤ 6 months) outcomes, including 6-min walk distance (6MWD) (MD = 7.52, 95% CI: 2.09, 12.94), modified Medical Research Council Dyspnea Scale (mMRC) (MD = -0.29, 95% CI: -0.41, -0.18), COPD assessment test (CAT) (MD = -1.77, 95% CI: -3.52, -0.02), HADS (MD = -0.44, 95% CI: -0.86, -0.03), and St. George’s Respiratory Questionnaire (SGRQ’s) activity, impact, and symptom scores. In the long term (> 6 months), although improvements persisted in 6WMD [MD = 12.89, 95% CI (-0.37, 26.14)], mMRC [MD = -0.38, 95% CI (-0.56, -0.21)], CAT [MD = -1.39, 95% CI (-3.83, 1.05)], Hospital anxiety and depression scale (HADS) [MD = -0.34, 95% CI (-0.66, -0.03)], and SGRQ’s Activity, Impact, and Symptom scores between intervention and control groups, statistically significant differences were observed only for mMRC and HADS. Without considering time factors, the intervention group exhibited some improvement in FEV1% predicted and the forced expiratory volume in the first one second (FEV1)/ forced vital capacity (FVC) (%) without statistical significance compared to the control group. Conclusion Telerehabilitation therapy demonstrates short-term benefits in enhancing patients’ daily activity capacity, improving respiratory function, and enhancing mental health status, thereby improving patients’ quality of life. However, further high-quality, large-sample RCTs are required to ascertain its long-term effectiveness conclusively. Trial registration This study protocol was approved and registered in PROSPERO: CRD 42024509154.